Terahertz on-chip sensing by exciting higher radial order spoof localized surface plasmons. (24th December 2019) - Zhou, Ji; Chen, Lin; Sun, Qingyun; Liao, Denggao; Ding, Li; Balakin, Alexey V.; Shkurinov, Alexander P.; Xie, Jingya; Zang, Xiaofei; Cheng, Qingqing; Zhu, Yiming
Abstract: We demonstrate higher radial order spoof localized surface plasmon (LSP) resonances excited by a planar plasmonic waveguide with a ladder-shaped unit as a unique platform for terahertz (THz) on-chip sensing. The frequency shifts induced by the different dielectric permittivities of edible oils for higher radial order spoof LSPs are more sensitive than those for the fundamental mode. Experimental and simulated results agree well with each other. The proposed structure is easily integrated and have potential applications in enhanced on-chip THz sensing.